Molecular characterization of drug resistant Mycobacterium tuberculosis isolates from different regions in South Africa - Falmer, Alecia Angelique (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2008.